Pengaruh Faktor Pola Asuh Orang Tua, Kompetensi Pedagogik Guru dan Motivasi Berprestasi terhadap Prestasi Belajar Siswa di SMA Negeri Satu Atap Lembongan - Candra Manik Maheyeti; I Putu Wisna Ariawan; Ni Luh Gede Erni Sulindawati (LP. Ma'arif Janggan Magetan, 2023)
The research in this thesis is motivated by the many teacher competencies that have not been achieved in accordance with the National Education System Law No. 20 of 2003 Article 39 Paragraph 2. And also the parenting style of parents who tend not to support children's education because they have to help parents because of work and economic demands. The type of research used by this research is quantitative research with an